The important role of processes such as synapsis and recombination during meiosis in sexual reproduction - Zhang Wenjia (BIO Web of Conferences)
Sexual reproduction is a process that involves the fusion of sperm and egg cells, producing genetic diversity and enhancing the ability of species to adapt to environmental changes. During the fertilization process, the formation of gametes is significant, and it is closely related to meiosis. Meiosis consists of seven major processes: two rounds of division, cytokinesis, crossing over, chromosome condensation, nuclear envelope breakdown and reconstruction, and spindle formation. Among these, the pairing, synapsis, and recombination of chromosomes can increase genetic diversity and are the central focus of meiosis. This article reviews the process of meiosis and the research on several related genes.